Long-Term Sequalae of Undiagnosed Intrusion of a Primary Tooth - Thikrayat Bani-Hani; Rona Leith; Anne C. O'Connell (MDPI AG, 2022)
Aims: This case demonstrates the adverse sequelae that can follow a traumatic dental injury at a young age. It also highlights the importance of taking a full history and undertaking a thorough exam, independent of the information in the referral. Case presentation: A 9-year-old boy was referred for treatment of "an extra tooth" and "hypoplastic and non-vital" maxillary left permanent incisors. Examination revealed a sinus tract labial to these incisors (21,22) with increased probing depth. However, the teeth were otherwise normal. The child sustained a fall as a baby and lost one of his primary teeth that was never recovered. Information collected suggested the most likely diagnosis was an undiagnosed complete intrusion of a primary incisor, with subsequent hypoplasia and malalignment in the developing teeth. Management included the removal of the intruded primary tooth and monitoring of the hypoplastic permanent incisors until complete eruption and root maturation. Aesthetic restorations were then provided. The patient was referred for orthodontic correction of the malalignment. Conclusion: Misdiagnosis and inappropriate management of dental trauma can cause additional damage. In this case, endodontic therapy in the permanent incisors was avoided by correct diagnosis. Clinicians have to correctly assess and justify their decisions on each individual case.